Amelia jane gets into trouble! - Blyton, Enid (Egmont London, 2001)
New editions, with new illustrations and new format, of all four Amelia Jane titles. Amelia Jane is big, bad and the terror of the toy cupboard! In this book, Sidney, the selfish teddy bear, has just come to the toy-cupboard. The toys are at their wits' end. If only they could teach Amelia Jane a lesson once and for all!